Transcription Factor EBF1 Over-Expression Suppresses Tumor Growth in vivo and in vitro via Modulation of the PNO1/p53 Pathway in Colorectal Cancer - Shen, Zhiqing; Chen, Youqin; Li, Li; Liu, Liya; Peng, Meizhong; Chen, Xiaoping; Wu, Xiangyan; Sferra, Thomas J.; Wu, Meizhu; Lin, Xiaoying; Cheng, Ying; Chu, Jianfeng; et al. (Frontiers in Oncology, 2020)
Early B cell factor 1 (EBF1) has been identified as an upstream transcription factor of the potential oncogene PNO1 and is involved in tumor growth of cultured colorectal cancer (CRC) cells. However, its expression, biological function, and underlying mechanism of action in most solid tumors remain largely unknown. We postulated that EBF1 has a role in the pathophysiology of CRC. We analyzed EBF1 mRNA expression in CRC tumor samples from several public databases and directly from banked tissues and found that EBF1 mRNA expression is lower in CRC tissue as compared to noncancerous colorectal tissue. Survival analysis of multiple datasets revealed that low EBF1 expression was correlated with shorter overall survival, relapse-free survival, and event-free survival in CRC patients. Transduction of lentiviral encoding full length EBF1 followed by in vitro and in vivo assays demonstrated that EBF1 over-expression in CRC cell lines suppressed cell growth by inhibiting cell viability, cell survival, and inducing cell cycle arrest and cell apoptosis. Mechanistic investigation indicated that EBF1 over-expression down-regulated PNO1 mRNA and protein expression, as well as transcriptional activity while up-regulating the protein expression of p53 and p21. These findings suggested that EBF1 is a novel potential tumor suppressor in CRC with possible prognostic value for the identification of patients at high-risk of relapse.